2005
DOI: 10.1160/th04-02-0091
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tissue factor-induced coagulation and platelet aggregation in flowing whole blood

Abstract: Photochemically induced thrombosis (a thrombin-dependent process) was measured in rats treated with moderate doses of anticoagulants, but which appeared to be unchanged. We considered the possibility that platelet-inhibiting agents, which also indirectly inhibit coagulation, would act as more potent antithrombotic agents. Inhibitors used as such were prostaglandin E1 (PGE1), which elevates cyclic AMP levels, and the P2Y12 ADP-receptor antagonist, AR-C69931MX. Effects of these agents were investigated in an ex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The fibrin surface was verified to recruit platelets, and to trigger platelet spreading, pseudopod extension and formation of small aggregates, consistent with platelet activation. The combination of PGE 1 /aspirin partially inhibited the control and QPD platelet adhesion to fibrin, consistent with their known attenuating effects on platelet adhesion to fibrin [33,34]. We confirmed that QPD platelet recruitment to a fibrin surface was associated with an increased fibrin degradation, likely mediated, at least in part, by platelet delivered u‐PA, as platelet activation inhibitors reduced the fibrin degradation.…”
Section: Discussionsupporting
confidence: 84%
“…The fibrin surface was verified to recruit platelets, and to trigger platelet spreading, pseudopod extension and formation of small aggregates, consistent with platelet activation. The combination of PGE 1 /aspirin partially inhibited the control and QPD platelet adhesion to fibrin, consistent with their known attenuating effects on platelet adhesion to fibrin [33,34]. We confirmed that QPD platelet recruitment to a fibrin surface was associated with an increased fibrin degradation, likely mediated, at least in part, by platelet delivered u‐PA, as platelet activation inhibitors reduced the fibrin degradation.…”
Section: Discussionsupporting
confidence: 84%
“…34 However, because this phosphorylation can be reversible as well, the relation between the integrin phosphorylation state and the presently studied delayed platelet disaggregation still needs to be established. This also holds for the cAMP/protein kinase A-mediated mechanism of integrin closure, which is likely to be distinct from the cAMP effect on Ca 2ϩ signal generation, 35 but is still unidentified.…”
Section: Discussionmentioning
confidence: 98%
“…The perfusion protocol was such that coagulation occurred at physiological, millimolar Mg 2ϩ , and Ca 2ϩ concentrations. 21 With wild-type blood, perfusion in the presence of tissue factor resulted in PS exposure and the formation of platelet aggregates, which gradually transformed to clots trapping erythrocytes ( Figure II, available online at http://atvb.ahajournals.org). TPLSM analysis indicated that the thrombi contained extensive networks of fibrin and aggregated platelets, which were surrounded by single PSexposing platelets.…”
Section: Components Of the Gpvi Signaling Pathway Determining Platelementioning
confidence: 99%